2018
DOI: 10.7906/indecs.16.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Digital Competency Review

Abstract: According to the European Union's expectations, the Hungarian government set its goal to raise the digital competence level of the population as its importance can no longer be questioned. The opportunity to increase the users' level of digital competency, and the examination of the results achieved will make the training more effective. Digital knowledge must be increased so as to make digital goods equally accessible to everyone. Most of the workplaces and professions require a certain level of digital liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 14 publications
2
29
0
Order By: Relevance
“…For example, Antosz () identified the competencies relevant to workers in the field of maintenance of equipment for production organizations. Nyikes () has done an overview of the digital competencies that people will need in the future, whereas Kinkel, Schemmann, and Lichtner () have reviewed the critical competencies that affect employee innovation. Several specific job profile competencies have been developed, for example, for information technology job profile (Benešová & Tupa, ) or general competence models that propose different levels and groups of competencies for Industry 4.0 (e.g., Hecklau et al, ; Prifti, Knigge, Kienegger, & Krcmar, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Antosz () identified the competencies relevant to workers in the field of maintenance of equipment for production organizations. Nyikes () has done an overview of the digital competencies that people will need in the future, whereas Kinkel, Schemmann, and Lichtner () have reviewed the critical competencies that affect employee innovation. Several specific job profile competencies have been developed, for example, for information technology job profile (Benešová & Tupa, ) or general competence models that propose different levels and groups of competencies for Industry 4.0 (e.g., Hecklau et al, ; Prifti, Knigge, Kienegger, & Krcmar, ).…”
Section: Introductionmentioning
confidence: 99%
“…In providing services online, mastery of this information technology must have an impact. Utilization of big data, cloud, social networks, and mobile devices should be able to achieve a higher level of collaboration than ever before [6]. Every employee needs to experience the benefits of being in this digital world.…”
Section: Proceedings Of the 6th International Conference On Educationmentioning
confidence: 99%
“…Results that indicate which phrases co-occurred most often within each of the clusters are presented in Figure 4. Analysis retrieved four main topics, i.e., (1) personnel development in learning organizations [32][33][34][35][36][37][38], (2) training techniques for personnel [39][40][41], (3) future engineering profile and engineering education [42][43][44], and (4) relational capabilities [45][46][47]. Although the total number of papers was 44, the cluster algorithm included 7 papers in Cluster 1 and 3 papers for the remaining clusters, since the topics of other papers were highly specific, and could not be assigned to any of the developed clusters.…”
Section: Topic Miningmentioning
confidence: 99%
“…Analysis of selected papers showed that there are three papers focused on personnel training techniques (Cluster 2). Papers that are presented have been written within a period of two years, which includes training to gather digital knowledge [39,41] and training updated with techniques and ideas coming from the industry world [40].…”
mentioning
confidence: 99%
See 1 more Smart Citation